ALUMINUM AND STEEL WELDING WITH 500 W FIBRE LASER - Dudenkovs, Raitis; Lazov, Lyubomir (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2023)
The study of the process of laser welding of various aluminum-steel joints is necessary to promote the possibility of realization of new products and designs in instrumentation and mechanical engineering. Laser welding, due to its many advantages, is considered a very promising process of joining different materials, although its application in industry is still limited. Welding aluminum with steel using laser sources is a challenging task mainly due to the formation of brittle intermetallic joints (IMC) at the joint interface. This paper aims to give a brief overview of some new research on laser welding of aluminum to steel, as well as to point out some of our initial laboratory research in this direction.[1]